PLANETARY THINKING FORMATION COMPONENTS OF FUTURE TECHNICAL UNIVERSITY ENGINEERS IN THE EDUCATIONAL INFORMATION ENVIRONMENT - Рахманов, Віталій Олегович (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2017)
The article defines and analyzes the planetary thinking formation components of future technical university engineers in the educational and information environment. The paper presents the principles of management of the educational process at the technical university, the implementation of which will improve the mechanism of students’ planetary thinking formation in the process of independent cognitive activity. It is the existence of various types of thinking that is caused by the peculiarity of future engineers specific activity at different stages of development